1996
DOI: 10.1111/j.1471-0307.1996.tb02494.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of starter level, draining time and aging on the physicochemical, organoleptic and rheological properties of feta cheese

Abstract: Feta cheese was made from ewe's milk using three different levels of starter (0.20, 0.50 and 0.75%) and two draining times (6 and 20 h). Cheese made with addition of 0.75% starter had a lower pH and moisture content than the cheeses made with 0.20 and 0.50% starter. With the increase in starter level there was also an increase in cheese fat content, although the fat in dry matter remained almost constant. The lower level of starter resulted in cheese with lower protein content, while other cheese components we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
4
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 14 publications
5
34
4
3
Order By: Relevance
“…Creamer and Olson (1982) suggested that the hydrolysis of α s1 -casein to α s1 -1-casein is responsible for early softening of high moisture cheeses. Pappas et al (1996) also suggested that increased degradation of α s1 -casein during ripening softens cheese texture. However, the fact that from 30 days onwards, the hardness of all the experimental Feta-type cheese increased could be due to the fact that the extent of proteolysis was probably not sufficient enough to compensate the loss of moisture in cheese towards the end of ripening period.…”
Section: Textural Attributesmentioning
confidence: 98%
“…Creamer and Olson (1982) suggested that the hydrolysis of α s1 -casein to α s1 -1-casein is responsible for early softening of high moisture cheeses. Pappas et al (1996) also suggested that increased degradation of α s1 -casein during ripening softens cheese texture. However, the fact that from 30 days onwards, the hardness of all the experimental Feta-type cheese increased could be due to the fact that the extent of proteolysis was probably not sufficient enough to compensate the loss of moisture in cheese towards the end of ripening period.…”
Section: Textural Attributesmentioning
confidence: 98%
“…Creamer and Olson (1982) suggested that the hydrolysis of α s1 -casein to α s1 -1-casein is responsible for early softing of high moisture cheeses. Pappas et al (1996) also suggested that increased degradation of α s1 -casein during ripening softens the cheese.…”
Section: Textural Characteristicsmentioning
confidence: 99%
“…A yoghurt culture or a combination of mesophillic and thermophilic lactic acid bacteria is used for large-scale production of Feta cheese (Tamime and Kirkegaard 1991). In fact, mesophilic LAB or a mixture of mesophilic and thermophilic strains are more suitable than using only thermophilic LAB or yoghurt culture for the high acidification rate that is essential for the production of high-quality Feta cheese (Kandarakis et al 2001;Pappa and Anifantakis 2001a, b;Pappas et al 1996).…”
mentioning
confidence: 99%
“…After the 1st day of cheesemaking all other starter combinations had a satisfactory fermenting activity and the desired pH (4.5-4.6) was reached within 3-4 d post-coagulation. The pH drop rate was higher than that observed by other researchers (Pappas et al 1996a, Pappas et al 1996b, Papageorgiou and Marth 1989. This is probably due to the fact that the strains used in this study had been selected among a total of 109 strains for being fast acid producers (Karageorgis et al 2006).…”
Section: Effect Of Starter Culture Combination On the Chemical Characmentioning
confidence: 53%
“…Οι υπόλοιποι συνδυασμοί (με ή/και με μεσόφιλα στελέχη) έδειξαν ικανοποιητική δραστηριότητα μετά την 1η ημέρα και το pH μειώθηκε σε όλα τα δείγματα στα επιθυμητά όρια (pH 4,5 -4,6) εντός 3 έως 4 ημερών. Ο ρυθμός πτώσης του pH ήταν μεγαλύτερος από αυτόν που παρατήρησαν άλλοι ερευνητές (Pappas et al 1996a, Pappas et al 1996b, Papageorgiou and Marth 1989. Αυτό οφείλεται μάλλον στο ότι στην έρευνα μας, τα μεσόφιλα στελέχη είχαν προεπιλεγεί από ένα σύνολο 109 στελεχών (Κα ραγεώργης και συν.…”
Section: επίδραση των συνδυασμών οξυγαλακηκών καλ λιεργειών στα χημικunclassified